Implementation of the Culturally Responsive Teaching (CRT) Approach Through the Development of an E-Module on Polyhedra Material Based on Papuan Cultures - Syamsulrizal Syamsulrizal; Pramusinta Ayu Lestari; Siti Salina Mustakim (Journal of Teaching and Learning Mathematics, 2026)
Flat-sided three-dimensional shapes are part of geometry that are closely connected to everyday life. However, in learning activities, many students still experience difficulties in understanding this material. On the other hand, cultural issues in Indonesia, particularly in Papua, are increasingly being eroded by the advancement of the times, gradually diminishing the nation’s cultural identity. Therefore, an appropriate learning approach is needed as a solution to these problems. This study aims to describe the results of implementing a mathematics e-module on flat-sided three-dimensional shapes based on Papuan traditional houses as a form of Papuan culture–based learning for junior high school students. The learning approach used is the Culturally Responsive Teaching (CRT) approach assisted by an e-module, with the goal of optimizing students’ understanding of flat-sided three-dimensional shapes. This research employed a pre-experimental method with a one-group pretest–posttest design. The population consisted of eighth-grade students of SMPN 10 Manokwari, and the sample was selected using a one-group experimental technique. The instrument used was a mathematical ability test. The results of the study show that: (1) the implementation of the CRT approach assisted by the e-module effectively increased students’ understanding of flat-sided three-dimensional shapes, as indicated by an N-Gain index of 0.46, or 46%, which falls into the medium category; and (2) there is a difference in students’ understanding before and after being taught using the CRT approach assisted by the e-module, with a gain mean of 33.78.